2008
DOI: 10.1253/circj.72.157
|View full text |Cite
|
Sign up to set email alerts
|

Heavily Calcified Coronary Lesions Preclude Strut Apposition Despite High Pressure Balloon Dilatation and Rotational Atherectomy In-Vivo Demonstration With Optical Coherence Tomography

Abstract: rossing the lesion, initial dilatation by balloons and final stent expansion can present a challenge to the operator's skill and experience with heavily calcified lesions (HCL), because of the highly angulated lumen of these lesions and their resistance to expansion. 1,2 If balloons cannot cross or be expanded and the poorly steerable, thin, uncoated Rotablator ® wire (Boston Scientific, Natick, MA, USA) can be advanced, rotational atherectomy can result in favorable lesion modification that facilitates lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 6 publications
(5 reference statements)
0
39
0
1
Order By: Relevance
“…Some retrospective studies have related ASM to stent thrombosis, but most of these studies enrolled only patients with stent thrombosis and in small numbers 24, 25, 26, 27. Conversely, Guo et al1 reported that 40% of ASM resolved at 13‐month follow‐up because of negative remodeling; this was similar in paclitaxel‐eluting stents and BMS with no deaths or stent thromboses related to the presence of stent malapposition at 1‐year follow‐up in either group.…”
Section: Discussionmentioning
confidence: 99%
“…Some retrospective studies have related ASM to stent thrombosis, but most of these studies enrolled only patients with stent thrombosis and in small numbers 24, 25, 26, 27. Conversely, Guo et al1 reported that 40% of ASM resolved at 13‐month follow‐up because of negative remodeling; this was similar in paclitaxel‐eluting stents and BMS with no deaths or stent thromboses related to the presence of stent malapposition at 1‐year follow‐up in either group.…”
Section: Discussionmentioning
confidence: 99%
“…Intravascular optical coherence tomography (OCT) is a newly developed intravascular imaging modality with a maximal spatial resolution of 10 μm, [13][14][15] which is approximately 10-fold higher than that of IVUS. The aim of the present study was to use intravascular OCT to analyze the time course of neointimal coverage of SES in the chronic phase, and to identify the predictive factors influencing delayed neointimal coverage of stent struts.…”
Section: Editorial P 2210mentioning
confidence: 99%
“…21 The recent imaging modality of optical coherence tomography has detected stent strut malapposition, which is a potential risk factor for restenosis or thrombosis because of the increased activity of fibrin and platelets, 22 after treatment of heavily calcified lesions, despite the use of high-pressure dilatation or ROTA. 23 Changes in strategy from the BMS to the SES era, including smaller diameter and longer stents, and smaller burr size in the ROTA-SES group, may be related to the poor outcome after ROTA-SES in the dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Heavily calcified lesions sometimes lead to suboptimal expansion and strut malapposition, which are potential risk factors for stent thrombosis after DES use, 13,26 even after ROTA and high-pressure balloon dilatation. 23 Patients with calcified lesions that require ROTA, but who may not have been adequately treated with angioplasty, have a potentially high risk of stent thrombosis, so careful long-term monitoring is required.…”
Section: Discussionmentioning
confidence: 99%